Organ transplants - Campbell, Andrew (Mankato, Minn. : Smart Apple Media, 2010)
"Discusses current practices of organ transplants, developments in science that make transplants possible, and the history of organ transplants as well as issues surrounding organ shortage and organ selling"--Provided by publisher.
Includes index.
Keywords: Transplantation of organs, tissues, etc; Artifical Organs; Transplants; Stem cell